Attribution of achievement in English as a second language (ESL) : a study in Universiti Teknologi MARA, Terengganu / Nurul Kamalia Yusuf - Yusuf, Nurul Kamalia (2012)
There have been a number of studies carried out on achievement in English as a second language (ESL). Some of the studies in the same area have been extended on the students' perceptions on how they view their success and what they perceived its cause(s) to be. Attribution is a term used to represent an act of establishing a reason to an event. However, studies on Malaysian's attributions are scanty and the results are often varied. Hence, this study was conducted to examine one of the causal attribution dimensions which is locus of control; internal and external as suggested by Weiner (1986). On the whole, this study tried to 1) identify the level of ESL achievement among the students, 2) examine the features of the success attributions, 3) investigate the differences in the internal success attribution and ESL achievement among students 4) investigate the differences in the external success attribution and ESL achievement among students and 5) understand the differences in External/ Internal attribution in gender. A set of questionnaire was distributed to 330 university students in Universiti Teknologi MARA, Terengganu. Only about 71.5% of the questionnaire were returned and analyzed once the reliability of the questions was gained. The result of the study revealed that the majority of the students were moderate achievers in ESL that attributed their success to both external and internal factors. However, they were more inclined to external success attributions. There were differences found in internal success attributions among students of different achievement levels. The students of good level have attributed to success significantly differently than those of moderate as well as weak achievements. The same goes to the students with moderate compared to those weak achievement levels. The similar case was established in the external success attributions. The students with good level of achievement have a significantly different attribution from those of moderate and weak levels as well as weak when viewed with moderate level. Lastly, there was no significant difference in the attribution of success achievement between males and females. In short, both external and internal attributions were notably ascribed to achievement especially the success in ESL and that teacher which is an external factor played a noteworthy role in the achievement. Though, it was also pertinent that one's attributions varied according to their level of achievement.